2017
DOI: 10.1002/cam4.1138
|View full text |Cite
|
Sign up to set email alerts
|

INST OX‐05‐024: first line gemcitabine, oxaliplatin, and erlotinib for primary hepatocellular carcinoma and bile duct cancers: a multicenter Phase II trial

Abstract: Hepatocellular Carcinoma (HCC) incidence is increasing in the USA. Gemcitabine (G) and oxaliplatin (O) are active in HCC and biliary duct cancer (BDC). Erlotinib (E) is an EGFR tyrosine kinase inhibitor (TKI) with known activity against both. We sought to evaluate the efficacy of the combination G+O+E. Patients with either of the two diagnosis were treated in a phase II trial. Simons 2 stage design was used. A disease‐control rate (DCR), complete response (CR) + partial response (PR)+ stable disease (SD) at 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The results showed a median overall survival (OS) of 9.9 months, with a 16-week PFS rate of 43%, demonstrating encouraging efficacy outcomes. Patt et al .’s phase II clinical study ( 115 ) did not demonstrate a significant survival benefit among HCC patients receiving combination therapy of oxaliplatin, gemcitabine, and erlotinib. Recent results from a multicenter phase II clinical trial indicated that the combination of bevacizumab and erlotinib, compared to sorafenib alone, did not affect the OS of patients with advanced HCC, but the combination therapy resulted in a longer median event-free survival and demonstrated superior safety and tolerability profiles ( 116 ).…”
Section: Erbb Inhibitors: Clinical Applications and Explorationmentioning
confidence: 99%
“…The results showed a median overall survival (OS) of 9.9 months, with a 16-week PFS rate of 43%, demonstrating encouraging efficacy outcomes. Patt et al .’s phase II clinical study ( 115 ) did not demonstrate a significant survival benefit among HCC patients receiving combination therapy of oxaliplatin, gemcitabine, and erlotinib. Recent results from a multicenter phase II clinical trial indicated that the combination of bevacizumab and erlotinib, compared to sorafenib alone, did not affect the OS of patients with advanced HCC, but the combination therapy resulted in a longer median event-free survival and demonstrated superior safety and tolerability profiles ( 116 ).…”
Section: Erbb Inhibitors: Clinical Applications and Explorationmentioning
confidence: 99%